Federal Reserve policy since 1979 - D. HAMBERG (PSL Quarterly Review, 2013)
The article considers the change in the federal reserve instruments that occurred since October 1979. Before then, the FED used bank reserves to establish an interest rate that would result in the desired level of the money stock. After 1979 the FED replaced the federal funds rate as its control variable with the volume of bank reserves. In principal, provided the will to adjust interest rates when the money stock is off target exists, two policies show little difference. Critics of the Fed’s policy prior to 1979 often confuse principal with practice. Then, Fed policy was closer to pegging the federal funds rate than to using it as a control over the quantity of money.